Lead-Lag compensators: analytical and graphical design on the Nyquist plane - Zanasi, R.; Cuoghi, S.; Ntogramatzidis, Lorenzo (IEEE, 2011)
This paper presents a design method for the synthesis of a general class of lead-lag compensators to exactly satisfy gain and phase margins specifications. A free parameter of the compensator is used as a degree of freedom in order to satisfy additional requirements on the phase and/or gain crossover frequencies. A graphical procedure for the compensator design on the Nyquist plane is presented with some numerical examples.